Hurricane Risk and Property Insurance in Poland - Bak, Joanna (Olsztyn Economic Journal, 2022)
The objective of this paper is to identify the current situation and the trends in the market of property insurance offering protection against hurricane risk. This paper presents data on strong winds in January and February 2022 in Poland and the damage caused by them. Information from the General Headquarters of the National Fire Service, from the Energa Group of Companies and from individual insurance companies was used. The analysis was performed for insurance market data, and it focused on group 8, Section II (insurance against the element risk). To this end, the Annual Reports of the Polish Insurance Chamber and the Financial Supervision Authority for the past five years were used. Climate changes carry with them catastrophic phenomena whose frequency is growing. These include hurricanes, which have been causing multi-million property losses in recent years. Insurance companies include various aspects in the protection, which enables the policyholder to customize the product to their needs. Clients opt for this type of protection increasingly often. The gross written premium in insurance against elements and the number of active insurance policies is growing. The premium amount increased by more than 46% during the study period, and the number of active insurance policies increased by nearly 19%.